Lack of Diffuseness in Wave Propagation in Lightweight Joist-Floor - Chung, H; Brunskog, J (Turkish Acoustical Society, 2007)
It is common to assume the wave field to be diffuse in often used simplified calculation procedures in building acoustics, such as Statistical Energy Analysis (SEA) or energy flow methods. It is a well known that such diffuseness assumption is not always valid. This paper presents one such example. The structures under consideration are rib-reinforced plate structures. These may be a lightweight floor/joist structure in a building or hull of a ship. The diffuseness, or rather the lack of diffuseness, in such 'ribbed-plate' structures is examined. The amount of power transported at an angle is calculated by means of the structural intensity in that direction.